Akibat Hukum bagi PPAT yang Mengungkapkan Data Pribadi Pihak yang Bertransaksi: Studi Perlindungan Hukum - Miranda Damayanti; Ery Agus Priyono (SIGn Jurnal Hukum, 2022)
This study will examine and analyze the legal consequences for LDMO disclosing the personal data of transacting parties. In addition, this study also aims to determine the legal protection for parties who suffer losses due to violations committed by the LDMO. This study uses a normative juridical method. The collection of primary, secondary, and tertiary legal materials is carried out using literature study techniques. The collected legal material is then analyzed using qualitative data analysis methods with a statute approach. The results show that LDMO will get a sanction of dishonorable dismissal, payment of compensation, imprisonment for a maximum of four years, and or a fine for a maximum of four billion rupiahs. In this case, if the LDMO is legally and convincingly proven to have violated the oath of office and caused loss to several parties by disclosure of personal data. At the same time, forming the LDMO Guiders and Supervisors Council is a form of legal protection for all parties who commit legal acts before LDMO. In this case, any party that suffers a loss can complain about the alleged violation committed by LDMO to the Guiders and Supervisors Council. In addition, any party that suffers a loss also gets compensation from LDMO as regulated in laws and regulations. Therefore, it is recommended that LDMO uphold the oath of office as a moral code regulated in the Code of Ethics and Head of the NLA Regulation. In this case, to maintain their profession’s dignity and public trust in their noble role (officium nobile).